(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
In accordance to the scientific sources the history of the research of obligate parasite phytotrophic fungi of right bank Steppe of Ukraine can be tentatively divided into three stages: 1) from the middle of the 19th century to the 60s of the 20th century, beginning with the first studies by J.H. Léveillé, Ya.Ya. Valts with L. Rishavi, and N.K. Sredinski to generalization of the results of numerous research data in the volumes of the “Identification guide of fungi of Ukraine”; 2) the 70–80s. This stage is characterized by active research of parasitic micromycetes of the steppe zone of Ukraine (including its right bank). The results of this research were summarized in the monograph “Рarasitic fungi of Steppe zone of Ukraine”; 3) the 90s of the 20th century to this day.